From lab to field: biological control of the Japanese beetle with entomopathogenic fungi - Graf, Tanja; Scheibler, Franziska; Niklaus, Pascal A.; Grabenweger, Giselher (Frontiers in Insect Science, 2023)
The Japanese beetle, Popillia japonica, is an invasive scarab and listed as quarantine organism in many countries worldwide. Native to Japan, it has invaded North America, the Azores, and recently mainland Europe. Adults are gregarious and cause agricultural and horticultural losses by feeding on leaves, fruits, and flowers of a wide range of crops and ornamental plants. Larvae feed belowground and damage grassland. To date, no efficient and environmentally friendly control measure is available. Larval populations of other scarab species such as Phyllopertha horticola and Melolontha melolontha are controlled by applying spores of the entomopathogenic fungi Metarhizium brunneum and Beauveria brongniartii to larval habitats. Here, we tested this control strategy against Japanese beetle larvae in grasslands, as well as spore spray applications against adults in crops. Using both, large-scale field experiments and inoculation experiments in the laboratory, we assess the efficacy of registered fungal strains against Japanese beetle larvae and adults. Metarhizium brunneum BIPESCO 5 established and persisted in the soil of larval habitats and on the leaves of adult’s host plants after application. However, neither larval nor adult population sizes were reduced at the study sites. Laboratory experiments showed that larvae are not susceptible to M. brunneum ART 212, M. brunneum BIPESCO 5, and B. brongniartii BIPESCO 2. In contrast, adults were highly susceptible to all three strains. When blastospores were directly injected into the hemolymph, both adults and larvae showed elevated mortality rates, which suggests that the cuticle plays an important role in determining the difference in susceptibility of the two life stages. In conclusion, we do not see potential in adapting the state-of-the-art control strategy against native scarabs to Japanese beetle larvae. However, adults are susceptible to the tested entomopathogenic fungi in laboratory settings and BIPESCO 5 conidiospores survived for more than three weeks in the field despite UV-radiation and elevated temperatures. Hence, control of adults using fungi of the genera Beauveria or Metarhizium is more promising than larval control. Further research on efficient application methods and more virulent and locally adapted fungal strains will help to increase efficacy of fungal treatments for the control of P. japonica.